Implementing The Military Barracks Program For Character Education In Purwakarta: A Sociocultural Educational Review - Mukti, Saepul; Rafsanjani, Mohammad Fikri; Fasya, Nizar Muhammad; Erihadiana, Mohamad (UNIVERSITAS PAKUAN, 2025)
The rising incidence of student delinquency, including truancy, fighting, and involvement in youth gangs, has prompted the implementation of a military-style rehabilitation program in Purwakarta Regency as an alternative strategy for addressing behavioral problems. This study aims to evaluate the program's implementation, stakeholder perceptions, and its impact on student attitudes and behavior. Employing a descriptive qualitative approach with a case study design, data were collected through interviews, observations, and document analysis. The findings indicate that the program effectively fosters short-term behavioral changes by enforcing strict discipline and routine. However, the changes often diminish after reintegration into the school environment due to a lack of sustained support. While parents generally respond positively, concerns persist regarding the psychological intensity of the intervention. The study also reveals a heavy reliance on external interventions due to inadequate internal counseling systems within schools. It concludes that although the military approach serves as an initial behavioral trigger, long-term transformation requires a shift toward more humanistic models involving restorative practices, trained school counselors, and holistic educational policies to ensure sustainable support for at-risk students